In Vitro additive effect on griseofulvin and terbinafine combinations against multidrug-resistant dermatophytes (Brazilian Journal of Pharmaceutical Sciences, 2018)
Griseofulvin (GF) and terbinafine (TF) are commonly used drugs to treat dermatophytosis, a fungal infection of the skin. Today there is an increase in drug resistance to these antifungals which highlight the need for alternative synergistic therapies. Minimum Inhibitory Concentration (MIC) of GF and TF were determined against fungi clinical isolates from local hospitals with values ranging 0.03−2.0 µg mL-1 and 0.24−4.0 µg mL-1, respectively. A checkboard test was used to determine the combination of GF:TF which could induce an additive effect against the fungi isolates Multidrug-resistant isolates showed susceptibility after treatment with 16:2 µg mL-1 GF:TF. An MTT assay further verified that GF and TF combinations have greater additive effect against pathological and multidrug-resistant isolates than antifungals alone. Herein we disclose GF:TF combinations that could constitute as a possible new anti-dermatophyte therapy.